Effect of confinement on the seismic performance of reinforced concrete exterior beam-column joints. Issue 1 (2nd January 2018) - Asha, P.; Sundararajan, R.
Abstract: Recent earthquakes have demonstrated that even when the beams and columns in a reinforced concrete frame remain intact, the integrity of the whole structure is undermined if the joint where these members connect fails. The detailing of joints play a crucial role in providing ductility and strength required to sustain large deformations and reversed stresses during earthquakes. In this paper, a non-conventional reinforcement detailing in the form of additional diagonal bars from column to beam is introduced in the beam–column joint specimens to shift the plastic hinge location from beam–column interface. Also four different confinements such as square hoop, square spiral, circular hoop and circular spiral were incorporated in the joint and column region and their effect on the seismic performance of specimens is investigated. Among the four specimens investigated, all the four were having their plastic hinges relocated to 2D distance from the beam–column interface and square spiral confined specimen had the overall best performance in terms of load-carrying capacity, load ratio, displacement ductility, energy dissipation, etc.